Notice: Payments for answers will end 4/10/2017. Click for more info.
Question and answer
Question not found
Ask a question
Not a good answer? Get an answer now. (Free)
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
Solve this proportion: x + 1 over 6 and x + 2 over 4. Here are the multiple choices: { - 4} {3} {1/2} { - 6} User: That is incorrect, please look at the multiple choices.
Weegy: How to Construct Better Multiple-Choice Tests This section is intended for school, college, [ [ and university teachers. When to use multiple-choice: advantages and disadvantages How to write a good multiple-choice question Advanced techniques for innovative multiple-choice questions Advanced techniques for testing higher level thinking Question Arrangement on Tests. Multiple-Choice Construction Checklist Frequently Asked Questions about Multiple-choice Multiple-Choice Glossary References: Useful textbooks and relevant websites ] ] (More)
Question
Expert Answered
Updated 8/6/2014 9:35:18 PM
1 Answer/Comment
-4 is the answer for x + 1 over 6 and x + 2 over 4.
(x+1)/6=(x+2)/4
(x+1)/3=(x+2)/2
2*(x+1)/3=x+2
2x+2=3(x+2)
2x+2=3x+6
3x-2x=2-6
x=-4.
Added 8/6/2014 9:27:22 PM
This answer has been confirmed as correct, not copied, and helpful.
Confirmed by jeifunk [8/6/2014 9:35:23 PM], Rated good by jeifunk
Solve this proportion: x + 1 over 6 and x + 2 over 4. Here are the multiple choices: { - 4} {3} {1/2} { - 6}
Weegy: The proportion for the equation x+1/6, x+1/2 is (1/6+x)+(1/2+x) = 2 x+2/3. (More)
Question
Expert Answered
Updated 8/6/2014 9:35:00 PM
1 Answer/Comment
-4 is the answer for x + 1 over 6 and x + 2 over 4.
(x+1)/6=(x+2)/4
(x+1)/3=(x+2)/2
2*(x+1)/3=x+2
2x+2=3(x+2)
2x+2=3x+6
3x-2x=2-6
x=-4.
Added 8/6/2014 9:28:51 PM
This answer has been confirmed as correct, not copied, and helpful.
Confirmed by jeifunk [8/6/2014 9:34:57 PM], Rated good by jeifunk
Solve the linear equation. -2x - 2 + 7(x + 1) = 2x - 4
Weegy: -2x - 2 + 7(x + 1) = 2x - 4; -2x - 2 + 7x + 7 = 2x - 4; 5x + 5 = 2x - 4; 5x - 2x = -4 - 5; 3x = -9; x = -9/3; x = -3 User: Solve and check the linear equation. 6x - 7 + 3(x + 1) = 4x - 6 (More)
Question
Expert Answered
Updated 8/5/2014 10:56:52 PM
1 Answer/Comment
6x - 7 + 3(x + 1) = 4x - 6;
6x - 7 + 3x + 3 = 4x - 6;
9x - 4 = 4x - 6;
9x - 4x = -6 + 4;
5x = -2;
x = -2/5
Added 8/5/2014 10:56:52 PM
This answer has been confirmed as correct, not copied, and helpful.
Solve the following system of equations, using the graphing method: y = 4 - 2x y = 7 - 3x
Weegy: Solve the following system of equations, using the graphing method: y = 4 - 2x y = 7 - 3x ? Answer: The addition method of solving systems of equations is also called the method of elimination. [ This method is similar to the method you probably learned for solving simple equations. You just need to add those equations but note that at least one of the coefficients of the 2 variables should be the same , or else multiply with suitable numbers to make it same. 3. 3x - 4y = -30 + 7x + 4y = 10 - - - - - - - - - - 10x = -20 x = 20/10 = -2 and then subst. this in any of the equations to get the value of y . ] User: So is this answer is (3,2) Weegy: So is this answer is (3,2)? Answer: yes User: Thank you! Weegy: Thank you! Answer: Welcom thanks for asking Weegy!. (More)
Question
Expert Answered
Updated 9/21/2014 6:34:54 AM
1 Answer/Comment
The answer for y = 4 - 2x , y = 7 - 3x is x = 3 ,y = -2 .
put 1th equation in the 2th equation, we can get :
4-2x = 7 - 3x
4-7 = -3x + 2x
-3 = -x
x = 3,

y = 4 - 2x
y = 4 - 2*3
y = -2


Added 9/21/2014 6:34:54 AM
This answer has been confirmed as correct, not copied, and helpful.
Confirmed by andrewpallarca [9/21/2014 10:25:51 AM], Rated good by andrewpallarca
Solve the following system of equations, using the graphing method: x + 2y = 4 2x - y = 3
Question
Not Answered
Updated 10/1/2014 6:22:14 AM
1 Answer/Comment
The solutions for the systems x + 2y = 4, 2x - y = 3 are x = 2, y = 1.
Multiply x + 2y = 4 by -2:
-2x - 4y = -8;
(-2x - 4y = -8) + (2x - y = 3):
-5y = -5;
y = 1;
Solve for x:
x + 2(1) = 4;
x + 2 = 4;
x = 4 - 2;
x = 2
Added 10/1/2014 6:22:14 AM
This answer has been confirmed as correct, not copied, and helpful.
27,403,183 questions answered
Weegy Stuff
S
P
Points 114 [Total 765] Ratings 0 Comments 114 Invitations 0 Offline
S
P
P
L
P
P
Points 55 [Total 1723] Ratings 0 Comments 55 Invitations 0 Offline
S
Points 21 [Total 21] Ratings 2 Comments 1 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 2 Comments 0 Invitations 0 Offline
S
Points 3 [Total 14] Ratings 0 Comments 3 Invitations 0 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
S
Points 1 [Total 1] Ratings 0 Comments 1 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.